The Culture of Driving under the Influence of Cannabis and Alcohol in Washington State. (March 2021) - Otto, Jay; Ward, Nicholas; Finley, Kari; Baldwin, Shelly; Grondel, Darrin
Traffic crashes are a significant public health concern killing more than 37, 000 people each year in the U.S. Poly-drug impaired driving is a growing factor in many fatal crashes. Research has shown that cannabis and alcohol (separately and combined) impair driving ability and increase crash risk. Washington State legalized recreational cannabis in 2014 and has since seen a steady increase in adult use of cannabis, and relatedly, drivers testing positive for compounds associated with cannabis. This study examined the behaviors and culture (e.g., shared values and beliefs) associated with driving under the influence of cannabis and alcohol of a representative sample of adults in Washington State. Most adults (91%) reported they did not drive within 2 hr of consuming cannabis and alcohol, had a negative attitude about that behavior (81%), and believed it was unacceptable (83%). Those drivers who reported they did drive within 2 hr of consuming cannabis and alcohol had different beliefs, for example that using cannabis after having too much to drink would calm them down and sober them up. This study examined the relationship between attitudes, behavioral beliefs, perceived injunctive and descriptive norms, perceived control beliefs, values, and assumptions and driving within 2 hr of consuming cannabis and alcohol.